Formulation and In vitro Evaluation of Kaffir Lime Fruit Peel Extract-Containing Gel for Sunscreen, Antioxidant, and Moisturizing Activity - Darsono, Farida Lanawati; Soegianto, Lisa (Pharmaceutical Sciences and Research, 2025)
Kaffir lime peel waste (Citrus hystrix) has antioxidant effects that have the potential to protect the skin from exposure to UV-A and UV-B rays, as well as moisturize the skin. This study aims to determine the effect of increasing the concentration of condensed extract of kaffir lime fruit peel on its effectiveness as an antioxidant, sunscreen activity, and moisturizer. The condensed extract was obtained by maceration using 96% ethanol. In this study, we tested hydrophilic gels consisting of 4 extract concentrations in their formula: F1 (7.5%), F2 (10%), F3 (15%), and F4 (20%). The research phase begins with the extract standardization process and gel formulation, followed by testing physical quality and efficacy as an antioxidant, sunscreen, and moisturizing activity. Experimental data from different batches and formulas were analyzed using the One-Way ANOVA statistical method. The condensed extract (20%) provides an IC50 value of 15.51 mg/mL. The results of the experiment showed that increasing the concentration of kaffir lime fruit peel extract could reduce the pH value, viscosity and increase the spreadability of the gel preparation. The SPF value increased with increasing extract concentration. It is included in the maximum protection category, while based on the % Erythema Transmission Value ≤ 1 and % Transmission Pigmentation of 3-40, it falls under the total block category. Increasing the concentration of a condensed extract of kaffir lime fruit peel in a hydrophilic gel base can increase its effectiveness as a UV protector and a moisturizer, with F3 (15%) as the best formula.